Food demand analysis of Indonesian households with particular attention to the poorest - Evita Hanie Pangaribowo; Daniel Tsegai (University of Bonn, Center for Development Research (ZEF), 2011)
The purpose of this study is to analyze the demand responses of Indonesian households to food prices, income changes and other socioeconomic factors. The underlying assumption here is that inadequate information on household food expenditure patterns which vary across income groups and regions may have its contribution to the persistence of food insecurity. We use the Indonesian Family Life Survey data and methodologically we employ an extended form of the Quadratic Almost Ideal Demand System model which in cludes demographic and regional factors. Results reveal the well known pattern that food demand behavior varies significantly between urban and rural households as well as income groups. The poorest households consume relatively more staple food as well as alcohol and tobacco goods while the richest households consume relatively more meat, snack and dried food. It is shown that the poorest households expenditure elasticity on alcohol and tobacco is high implying that the poorest households transfer their extra resources on alcohol and tobacco goods instead of more nutritious food items. Results also show that price and expenditure elasticities have changed across time (1997-2007). Own price elasticities have increased for most food items implying that people have become more responsive to changes in prices. In contrast, the expenditure elasticity has declined for most food items (except for 'alcohol and tobacco goods') which would imply welfare improvement since the 1997 crisis.
Keywords: D11; D12; 330; food demand; QUAIDS; Indonesia